Nematicidal activity of silver nanoparticles from the fungus Duddingtonia flagrans - Barbosa ACMS (Dove Medical Press, 2019)
Anna Claudia Mombrini Silva Barbosa,1 Laryssa Pinheiro Costa Silva,1,2 Carolina Magri Ferraz,1 Fernando Luiz Tobias,1 Jackson Victor de Araújo,3 Barbara Loureiro,1 Gracilene Maria Almeida Muniz Braga,4 Francielle Bosi Rodrigues Veloso,4 Filippe Elias de Freitas Soares,3 Marcio Fronza,4 Fabio Ribeiro Braga1 1Parasitology and Biological Control Laboratory, Universidade Vila Velha, Vila Velha, Brazil; 2Morphology Department, Federal University of Espírito Santo, Vitória, Espírito Santo, Brazil; 3Department of Veterinary Medicine, Universidade Federal de Viçosa, Viçosa, Brazil; 4Department of Pharmaceutical Sciences, Universidade Vila Velha, Brazil Background: Helminth parasites cause morbidity and mortality in both humans and animals. Most anthelmintic drugs used in the treatment of parasitic nematode infections act on target proteins or regulate the electrical activity of neurons and muscles. In this way, it can lead to paralysis, starvation, immune attack, and expulsion of the worm. However, current anthelmintics have some limitations that include a limited spectrum of activity across species and the threat of drug resistance, which highlights the need for new drugs for human and veterinary medicine.Purpose: Present study has been conducted to determine the anthelmintic activity of silver nanoparticles (AgNPs) synthesized from the extract of nematophagous fungus, Duddingtonia flagrans, on the infecting larvae of Ancylostoma caninum (L3). Methods: The nanoparticles were characterized by visual, ultraviolet, Fourier-transform infrared spectroscopy, transmission electron microscopy (TEM) analysis, and X-ray diffraction. The in vitro study was based on experiments to inhibit the motility of infective larvae (L3), and the ultrastructural analysis of the nematode was performed by images obtained by TEM. Results: The XRD studies revealed the crystalline nature of the nanoparticles, and FTIR results implied that AgNPs were successfully synthesized and capped with compounds present in the extract. The results showed that the green synthesis of AgNPs exhibited nematicidal activity, being the only ones capable of penetrating the cuticle of the larvae, causing changes in the tegmentum, and consequently, the death of the nematode. Conclusion: The extract of the fungus D. flagrans is able to synthesize AgNP and these have a nematicidal action. Keywords: nanotechnology, biomedicine, nanoparticles, helminths, biological control